Hand Signs for Lip-syncing: The Emergence of a Gestural Language on Musical.ly as a Video-Based Equivalent to Emoji. (October 2017) - Rettberg, Jill Walker
Video-based communication is increasingly common online. This article looks at the hand signs that are used in lip-syncing videos on the app musical.ly and argues that they constitute a codified, non-verbal language of pictograms that is equivalent to emoji in text-based communication. Seeing the lip-syncing videos as performances allows us to situate the hand signs as the latest development in a long history of formalized gestures for theatrical performance. By recognizing this emergent gestural language as a performative element of online communication, we can reinterpret emoji and other forms of visual supplement to writing as part of a larger emerging system of communication where visual signs are becoming integrated into verbal language, not only in written language but also in video-based communication.